The Validity Of Wali Muhakkam In The Practice Of Unregister Marriages And Legal Consequences At East Aceh Regency - Said Rizal; Pagar -; Zainul Fuad (Faculty of Law, Universitas Pekalongan, 2023)
This study aims to determine and analyze the process of unregistered marriage through the guardian of Muhakkam. This study uses an empirical juridical method with a statutory and socio-legal approach. The results of this study indicate that the unregister marriage process carried out by the people in East Aceh by the guardian of Muhakkam still follows the understanding of the tengku and ulama but is not in accordance with the Marriage Act. Marriage without legal evidence and registration at the KUA can bring harm. There are several factors that influence the practice of unregistered marriages, including economic factors, not getting parental approval, low levels of education, lack of understanding and awareness of the importance of registering marriages, the absence of sanctions for perpetrators of unregistered marriages, and problems with polygamy permits